The effect of rGO on optical properties of neodymium nanoparticles doped tellurite glass system / Hafizah Rajaa Shaari ... [et al.] - Rajaa Shaari, Hafizah; Noorazlan, Muhammad; Abu Bakar, Suriani; Yahya, Azlina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Nanomaterials based on graphene have outstanding properties, particularly in terms of optical performance. Using melt-quenching and low-cost spray coating procedures, we effectively generated a series of reduced graphene oxide-coated tellurite glasses doped with neodymium nanoparticles, denoted as rGO-ZBTNd (NPs) glasses. An X-ray diffraction study of glass samples validated the glass system's amorphous structure. FESEM morphological analysis was used to evaluate the appearance of rGO on the glass substrate and revealed the dispersion of rGO. UV-Vis spectroscopy was used to determine different absorption bands. The refractive index value calculated using the Dimitrov and Sakka equation was found to be more than n > 2.000 and in the range of 2.339 to 2.657 when compared to uncoated samples. On the basis of these findings, a new method involving rGO deposited on tellurite glass has been developed to improve the tellurite glass currently utilised in laser applications